Differences Between Lovastatin and Simvastatin Hydrolysis in Healthy Male and Female Volunteers: Gut Hydrolysis of Lovastatin is Twice that of Simvastatin - Tom B. Vree; Erik Dammers; Ivan Ulc; Stefan Horkovics-Kovats; Miroslav Ryska; IJsbrand Merkx (The Scientific World Journal)
The aim of this pharmacokinetic evaluation was to show the effect of the extra methyl group in simvastatin on esterase hydrolysis between lovastatin and simvastatin in male and female volunteers. This study was based on the plasma concentration-time curves and the pharmacokinetics of lovastatin and simvastatin with its respective active metabolite statin-β-hydroxy acid obtained from two different bioequivalence studies, each with 18 females and 18 males. Results were: 1-The group of female volunteers showed a higher yield of the active metabolite β-hydroxy acid than the group of males (p < 0.002) for both lovastatin and simvastatin. This difference was not related to the body weight of both groups. 2-In the male/female groups, subject-dependent yield of active metabolite β-hydroxy acid was demonstrated, which was independent of the formulation. The variation in plasma/liver hydrolysis resulted in a fan-shaped distribution of data points when the AUCt lovastatin was plotted vs. that of the β-hydroxy acid metabolite. In the fan of data points, subgroups could be distinguished, each showing a different regression line and with a different Y-intercept (AUCtβ-hydroxy acid). 3-Lovastatin hydrolysis was higher than simvastatin hydrolysis. 4-It was possible to discriminate between hydrolysis of both lovastatin and simvastatin by plasma/liver or tissue esterase activity.